GENERAL DEVELOPMENT EXERCISES AND THEIR CONDUCT IN FORMING A HEALTHY LIFESTYLE IN STUDENTS (Spectrum Journal of Innovation, Reforms and Development, 2022)
In modern conditions, the relevance of physical education of students is unquestionable, because physical education and sports lead to the optimization of a person's physical health and development together with his mental qualities. This article is based on the use of sets of general developmental exercises in the course of physical education classes as a complex pedagogical tool for educating students. Conclusions and recommendations presented by the author are suggested to be taken into account in physical education classes with schoolchildren.